Genetic diversity and structure of tobacco in greece on the basis of morphological and microsatellite markers - Apostolos Kalivas (2018)
© Crop Science Society of America. Oriental tobacco varieties have greater aroma value, and consumer demand for these varieties is now greater than ever. Yet our knowledge of morphological and genetic diversity within diverse gene pools of cultivated oriental tobacco (Nicotiana tabacum L.) varieties is limited. Phenotypic and genetic analysis of these genotypes is important for the improvement of tobacco varieties. Information on morphology and genetics could help toward future germplasm maintenance and selection of suitable materials for breeding elite varieties. This study presents an assessment of morphology and genetic diversity for 34 tobacco cultivars maintained in an ex situ GeneBank collection. Data of 36 traits, describing phenology, plant morphology, and leaf quality, were recorded over 3 yr and analyzed using principal component analysis. Euclidean distance metric and the Ward’s agglomeration method were used in an unsupervised hierarchical cluster analysis of the 34 different cultivars used. The tobacco cultivars were classified into three main clusters, suggesting that the characterized tobacco collection has high potential for specific breeding goals. Furthermore, the 34 tobacco cultivars were genotyped with 10 microsatellite markers. High levels of polymorphism were detected, and 63 distinctive alleles were identified; on average 6.3 alleles per primer. Both the principal component analysis, derived from the morphological data, and the unweighted pair group method, with arithmetic mean from the molecular analysis, clustered the tobacco cultivars according to their type (oriental and flue-cured tobacco). Furthermore, a Bayesian clustering approach analysis allowed a more detailed grouping of subpopulations.